‘It’s important that we learn too’: Empowering parents to facilitate participation in physical activity for children and youth with disabilities - Willis, C.; Reid, S.; Elliott, Catherine; Nyquist, A.; Jahnsen, R.; Rosenberg, M.; Girdler, Sonya (Informa Healthcare, 2017)
Aim: The actions and behaviors of parents have been identified as key factors that influence a child’s participation in physical activity. However, there is limited knowledge of how parents can be supported to embody facilitative roles. This study aimed to explore how an ecological intervention encourages parents of children with disabilities to develop as facilitators, to enable ongoing physical activity participation in a child’s local environment. Methods: A qualitative design using grounded theory was employed. Forty four parents (26 mothers, 18 fathers) of 31 children with a range of disabilities (mean age 12y 6m (SD 2y 2m); 18 males) partaking in the Local Environment Model intervention at Beitostolen Healthsports Centre in Norway participated in the study. Data were derived from the triangulation of semi-structured interviews and participant observation. Data analysis was an iterative approach of constant comparison, where data collection, memo writing, open, axial and selective coding analysis, were undertaken simultaneously. Findings were consolidated into a model describing the central phenomenon and its relationship to other categories. Results: Thematic concepts uncovered in this study describe a social process of parent learning and empowerment, comprising three primary components; (i) active ingredients of the intervention that enabled learning and empowerment to transpire, (ii) parent learning and empowerment as a process, and (iii) related outcomes. Conclusion: A family-centered approach, encompassing family-to-family support, may enhance physical activity participation outcomes for children and youth with disabilities.